Factors of development of legal culture of modern Russia - Snashkov S. A. (Law, Economics and Management, 2022)
The article presents an analysis of factors that significantly affect the processes of formation and development of the legal culture of modern Russia. The author focuses on legal policy and legal education, characterizing their features and levels of interaction with the phenomenon of legal culture.
Keywords: правовое образование; правовая культура; legal education; legal culture; правовая политика; legal policy; правовые качества личности; гуманизация права; legal personality qualities; humanization of law